Excitation of Arch and Suspension Bridges by Subwires - Noriaki Hiwatashi; Yoji Mizuta; Yutaka Ishihara; Itio Hirai (Shock and Vibration)
A force generation method using a subwire for arch and suspension bridges is proposed. The subwire is connected to the arch or the cable of the bridge through rollers. The uniform force produced by pulling and releasing the pretensioned subwires acts on the bridge as an externalforce. A new device called “the resonance force generator” is also developed to excite the bridges by applying a small force. To verify the proposed concept, a stress ribbon bridge was excited with the resonance force generator.